THE WAYS OF IMPROVING THE GOVERNMENTAL REGULATION OF TOURISM ACTIVITY IN UKRAINE - О. Davydova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The areas of state regulation of tourism activity in Ukraine, such as legal, economic, social and information areas are highlighted. Each of these areas are analyzed and the implementation of the concession agreement as well as the investment tax credit are proposed in order to stimulate the development of tourism activity in the country. It is mentioned, that one of the main tools of development of the territories is to promote the tourism brand through creating a positive tourism image via information. It was suggested to update the web page of the The State Agency of Ukraine for Tourism and Resorts and to create a online rating of local tour operators. It is found out that promising types of national tourism are children, family, green and business types of tourism.